Microfinance and Green Energy Lending: First Worldwide Evidence - Gregor Dorfleitner; Davide Forcella; Quynh Anh Nguyen (Credit and Capital Markets – Kredit und Kapital, 2020)
The increasing requirement for action on climate change in developing countries has led to the inclusion of environmental aspects in microfinance objectives, in addition to social and financial performance, and hence to the appearance of green microfinance. To date, financing for modern energy service has proven to be an attractive option to offset adverse climate change related effects for the poor. This article sheds some light on factors predicting clean energy finance involvement of MFIs. By using a worldwide survey among microfinance institutions on rural lending and IT solutions implemented by YAPU Solutions, this study investigates how institutional characteristics and economic growth relate to green energy micro-credit. The findings provide evidence of a significantly positive relationship between the maturity and business sustainability of an MFI and the likelihood of offering green energy loans. Moreover, MFIs managed by female managers and located in wealthy countries are less willing to commence the finance of green energy.
Keywords: G21; Q01; Q42; 330; Microfinance institutions; Green energy financing; Clean energy; Sustainable Development Goals